2012
DOI: 10.4271/2012-01-0689
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Loss Reduction of Highly Dispersed Spray Combustion with Restricted In-Cylinder Swirl and Squish Flow in Diesel Engine

Abstract: Recently, there has been an increasing awareness of environmental and energy problems, which are global in scale. Diesel engines have better fuel consumption than gasoline engines, and there are great hopes for them because they are more flexible in terms of fuel diversification. However, diesel engines have more NOx and smoke than gasoline engines, and thus require expensive fuel injection components and emission control devices to clean these emissions. Inagaki et al. 1) proposed a new combustion concept tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The purpose of this geometry was to modify the squish flow in order to enhance unburned products oxidation in this zone. Stepped geometry resulted in 4.6% lower piston surface than stock piston, which should limit heat transfer [41]. The second geometry was named as bathtub due to its similitude to the piston used in [40], but it is worthy to note that the central part of the piston used in the current work is not completely flat as in previous literature is.…”
Section: Piston Bowl Geometriesmentioning
confidence: 92%
“…The purpose of this geometry was to modify the squish flow in order to enhance unburned products oxidation in this zone. Stepped geometry resulted in 4.6% lower piston surface than stock piston, which should limit heat transfer [41]. The second geometry was named as bathtub due to its similitude to the piston used in [40], but it is worthy to note that the central part of the piston used in the current work is not completely flat as in previous literature is.…”
Section: Piston Bowl Geometriesmentioning
confidence: 92%
“…As the result of these studies, TSWIN developed first in the world has been adopted to the 2.8 L ESTEC 1GD diesel engine. 25 No remarkable damage was detected on the insulation coating throughout every durability tests before the start of production. In this application, it was confirmed that TSWIN can be used together with low heat rejection combustion systems such as with low swirl and low squish apparatus, as the additional item to gain better thermal efficiency.…”
Section: Summary/conclusionmentioning
confidence: 96%
“…By using the low luminosity combustion fuel, radiative heat transfer should have been reduced compared to that of normal diesel fuel combustion. Even if the contribution of radiation is about 10% of total wall heat transfer in diesel combustion with normal diesel fuel, 24,25 it is considered that the influence could be limited and it would be possible to ensure the temperature swing phenomenon. The engine operating condition is 1200 rpm, 50% load, and the fuel quantity of about 38 mm 3 /stroke.…”
Section: Temperature Swing Measurement Of Piston Top Surfacementioning
confidence: 99%
“…The first geometry was named as steeped and maintains the stock piston central geometry with a modified transition to the squish region, as shown in Figure 2. The aim of this geometry is to modify the squish flow in order to facilitate the unburned products oxidation and to limit heat transfer in this region [30]. The designed geometry resulted in 4.6% reduced piston surface versus the stock piston.…”
Section: Piston Bowl Geometriesmentioning
confidence: 99%